STUDI KOMPARATIF TARI FALUAYA DI NIAS SELATAN DENGAN TARI FALUAYA DI MEDAN - Laurensia Dora Melisa (Universitas Negeri Medan, 2015)
The Research aimed to know how comparison of Faluaya dance in Niasnese with Faluaya dance in Medan. The population of this research are some cuture figure of district Bawömataluo and Simalingkar, artists who know and concerned in the dance. The sample are; culture figure, artist and people who concerned in the dance itself. Descriptive qualitative research was used in this research. To got the data, researcher did field observation, video, interview and documentation. The finding of this research pursuant to gathered data, can know that dance of Faluaya in Niasnese and Medan there are equation as well as difference. Created from victory expression all society of Niasnese of enemy attacking land, groun power of then, conducted with singing and dancing. Society of Nias in Medan, making dance of Faluaya as one of the dance expressing etnical identy of them, by showing how selfregard a seen young man of its responsibility to orderliness of native land. In Nias, dancer of Faluaya tribe sall Nias itself, while in Medan do not be obliged from tribe of Nias. But both this dance use is same property, that is baluse (shield), toho (tombak) and tolögu (sword). Square and cicle represent floor pattern wich is often used n both this dance, however in Medan heve there are addition of of the floor pattern wich adapted for choreographer. By dress black chromatic at vest and interior at exterior. There ara same colour type of vest which commonly use by dancer of Faluaya in Nias, there is which black elementary materials, with colour of ornament red, black and turn yellow and also cloth turn yellow the so-called with göndöra as subordinate, there is also made brown chromatic vest of sea grass an bark. Manner move at dance of Faluaya in Nias have some motion motif an its movement still original and not affect by other ethnical. Square and circle represent floor pattern wich is often used in both this dance, however in Meda have there are addition of often floor pattern which adapted for its choreographer.